HUBUNGAN STANDAR PELAYANAN ANTENATAL CARE DAN PENDIDIKAN BIDAN DENGAN MUTU PELAYANAN KEBIDANAN DI UPT PUSKESMAS PA'BENTENGANG - Akib, Resky Devi; Ediyono, Suryo; Suardi, Hadijah (Jurnal Midwifery, 2026)
Background Antenatal care is a health service by health workers for mothers during their pregnancy problems, carried out in accordance with antenatal care service standards set out in midwifery service standards. Antenatal care is an effort to maintain maternal health during pregnancy, as well as an effort to reduce maternal morbidity and mortality rates. The research method The population in this study were all midwives on duty at the Pa'bentengang Health Center UPT, Bantaeng Regency, totaling 30 people. The sample in this study were midwives on duty at the KIA room of the Pa'bentengang Health Center UPT, Bantaeng Regency, totaling 30 people using Total Sampling The results The dominant respondents had D3 education as many as 23 people (76.7%) and D4 as many as 7 people (23.3%). The dominant respondents with good quality of midwifery services were 25 people (83.3%) and less good as many as 5 people (16.7%). There is a relationship between antenatal care service standards and the quality of midwifery services with a value of ρ = 0.031 <from α = 0.05. There is a relationship between education and the quality of midwifery services at the KIA Polyclinic with a value of ρ = 0.022 <from α = 0.05 Conclusion: It is expected that midwives on duty in the ANC section will improve their performance and attention in providing information about antenatal care (ANC) visits.